The use of culture and structure as a tool to guide competitive advantage: a behavioral model / Sarah Rikatmua Lukolm ... [et al.] - Rikatmua Lukolm, Sarah; Abbas, Muffaddal; Ali Sibtain, Majdi Amr; Monsef, Sanaz (2020)
This article proposes a descriptive model explaining the roles and relationships of organizational culture and structure in guiding employee behavior toward strategic objectives, which explores dynamic relationships between organizational culture, strategy, structure, and operations of both an organization's internal and external environment.One of the assets is at least working knowledge within individuals and groups residing within the organization. It is possible to create an organization that has an appropriate culture and structure to realize the potential locked into these assets (Banks, 1999). In this paper, there are presented various attempts to determine what is organizational structure and culture. The paper also shows the influence of the organizational culture and structure of the project team on the results of the project, which refers directly to organizational performance. The main advantages is also attached to the project-oriented organization and compared to some types of organizational cultures. Finally, it is recommended that there is a way, which should develop the project-oriented organizational culture for knowledge management and effectively managing for better relationship with environment.